Potential anticancer activity of protocatechuic acid loaded in montmorillonite/Fe3O4 nanocomposites stabilized by seaweed Kappaphycus alvarezii - Yew, Yen Pin; Shameli, Kamyar; Shaza Eva M,; Yuki, Nagao; Teow, Sin Yeang *; Lee, Kar Xin; Eleen Dayana, M. I. (Elsevier, 2019)
Superparamagnetic magnetite nanocomposites (Fe3O4-NCs) were successfully synthesized, which comprised of montmorillonite (MMT) as matrix support, Kappaphycus alvarezii (SW) as bio-stabilizer and Fe3O4 as filler in the composites to form MMT/SW/Fe3O4-NCs. Nanocomposite with 0.5 g Fe3O4 (MMT/SW/0.5Fe3O4) was selected for anticancer activity study because it revealed high crystallinity, particle size of 7.2 ± 1.7 nm with majority of spherical shape, and Ms = 5.85 emu/g with negligible coercivity. Drug loading and release studies were carried out using protocatechuic acid (PCA) as the model for anticancer drug, which showed 19% and 87% of PCA release in pH 7.4 and 4.8, respectively. Monolayer anticancer assay showed that PCA-loaded MMT/SW/Fe3O4 (MMT/SW/Fe3O4-PCA) had selectivity towards HCT116 (colorectal cancer cell line). Although MMT/SW/Fe3O4-PCA (0.64 mg/mL) showed higher IC50 than PCA (0.148 mg/mL) and MMT/SW/Fe3O4 (0.306 mg/mL, MMT/SW/Fe3O4-PCA showed more effective killing towards tumour spheroid model generated from HCT116. The IC50 for MMT/SW/Fe3O4-PCA, MMT/SW/Fe3O4 and PCA were 0.132, 0.23 and 0.55 mg/mL, respectively. This suggests the improved penetration efficiency and drug release of MMT/SW/Fe3O4-PCA towards HCT116 spheroids. Moreover, concentration that lower than 2 mg/mL MMT/SW/Fe3O4-PCA did not result any hemolysis in human blood, which suggests them to be ideal for intravenous injection. This study highlights the potential of MMT/SW/Fe3O4-NCs as drug delivery agent